2012
DOI: 10.1002/eji.201242398
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effects of high‐dose IgG on TNF‐α‐activated human coronary artery endothelial cells

Abstract: High-dose infusion of IgG (IVIG) is used to treat autoimmune and inflammatory diseases, including Kawasaki disease (KD). Although the immunomodulatory effects of IVIG on blood cells such as macrophages have been well studied, its effects on tissue cells remain unclear. Here, we show that high-dose IgG specifically and completely inhibited TNF-α-induced, but not IL-1β-induced, secretion of proinflammatory cytokines such as G-CSF and IL-6 by cultured human coronary artery endothelial cells (HCAECs). Highdose IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 43 publications
(49 reference statements)
2
28
0
1
Order By: Relevance
“…The apparently exclusive IL‐1β dependence of HCAEC activation by TLR‐4–stimulated human monocytes is remarkable, as other studies have demonstrated that HCAECs were responsive to recombinant TNF with overlapping profiles of induced gene expression in response to IL‐1β . However, an enhanced sensitivity of HCAECs toward IL‐1β, in terms of IL‐6 release, has already been suggested .…”
Section: Discussionmentioning
confidence: 85%
“…The apparently exclusive IL‐1β dependence of HCAEC activation by TLR‐4–stimulated human monocytes is remarkable, as other studies have demonstrated that HCAECs were responsive to recombinant TNF with overlapping profiles of induced gene expression in response to IL‐1β . However, an enhanced sensitivity of HCAECs toward IL‐1β, in terms of IL‐6 release, has already been suggested .…”
Section: Discussionmentioning
confidence: 85%
“…To date, a number of possible mechanisms for the immunomodulatory and anti-inflammatory effects of IVIG therapy have been described [18,19], including anticomplement effects [20], anti-idiotypic neutralization of pathogenic future science group www.futuremedicine.com autoantibodies [21], immune regulation via an inhibitory Fc receptor [16,22], enhancement of regulatory T cells [23] and inhibition of Th17 differentiation [24]. Thus, IVIG may mediate a wide variety of biological and immunomodulatory effects via various types of blood cells [24]. When considered together, these immunomodulatory effects of IVIG products might be beneficial in COVID-19 disease management, but this needs to be confirmed clinically.…”
Section: Discussionmentioning
confidence: 99%
“…IVIG products have been demonstrated to be effective in the treatment of inflammatory disorders [16]. To date, a number of possible mechanisms for the immunomodulatory and antiinflammatory effects of IVIG therapy have been described [17,18], including anticomplement effects [19], anti-idiotypic neutralization of pathogenic autoantibodies [20], immune regulation via an inhibitory Fc receptor [16,21], enhancement of regulatory T cells [22] and inhibition of Th17 differentiation [23]. Thus, IVIG may mediate a wide variety of biological and immunomodulatory effects via various types of blood cells [23].…”
Section: Discussionmentioning
confidence: 99%